Deportation of South Sudanese from Israel - Lijnders, L (Refugee Studies Centre, University of Oxford, 2013)
Israel’s aggressive campaign of arrest and deportation of South Sudanese asylum seekers contravenes the principle of non-refoulement and international standards for voluntary, dignified return.